The red blood cells cytometric characteristics of young fresh-water fish of various families - Sharamok, T.; Yesipova, N.; Kurchenko, V. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2022)
The morphometric indices of red blood cells of young fish of various species inhabiting coastal zones of the water bodies were studied. The subjects of the research were the fish of four families: Carp (Alburnus alburnus, Carassius gibelio, Rhodeus amarus, Abramis brama, Rutilus rutilus), Needles (Syngnathus abaster nigro lineatus), Centrarchidae (Lepomis gibbosus), Loaches (Cobitis taenia taenia), Gobies (Neogobius fluviatilis). The hydroecological conditions were characterized by an intense oxygen regime, high content of phosphates, and heavy metals (zinc). The fish peripheral blood was taken from the tail vein; smears were made according to the classical Romanowsky-Giemsa method. Our research showed that the red blood cells of young fish belonging to the ecological group of inactive and unpretentious species (Neogobius fluviatilis, Carassius gibelio) had the largest cross-sectional area and a high index of nuclear-cytoplasmic ratio. The indicators of erythrocyte eccentricity were the highest in the active fish with high energy costs (Alburnus alburnus, Lepomis gibbosus). The largest number of erythrocytes with pathological events (cytolysis, karyolysis, pyknosis, poikilocytosis) was observed in the young Alburnus alburnus (14%), and the smallest one in Rhodeus amarus and Lepomis gibbosus (2–4%). In the individuals of Syngnathus abaster nigro lineatus affected by parasitic nematodes of the genus Ascaris, the number of erythrocytes with pathologies increased to 81%. Under the toxic load, destabilization of the fish circulatory system begins with the appearance of the young forms of erythrocytes as compensation for depleted mature erythrocytes and ends with the mass destruction of mature erythrocytes. Given these patterns, as well as the relatively low number of young ballast forms of erythrocytes and mature erythrocytes with pathological features, we can assume that the state of the red blood cells in the studied young fishes meets the conditional norm, with the exception of the blood of Syngnathus abaster nigro lineatus infected with parasites. In our opinion, the main characteristics of the fish red blood that reflect the fishes’ adaptive capacities are as follows: eccentricity ratio of erythrocytes, the nuclear-cytoplasmic ratio, ratio of the young ballast forms of erythrocytes, and the relative number of erythrocytes with pathology.